Blue Flag: a Symbol of Environmental Protection - Ioan Petroman; Oliver Amzulescu; Horia Sărăndan; Cornelia Petroman; Ștefan Coman; Dora Manuela Orboi; Marcela Ivu (Scientific Papers Animal Science and Biotechnologies, 2023)
Blue Flag is a high standard symbol of environmental protection and it is awarded to the beaches and agreement ports by the Foundation of Education for the Environment. The beaches having been awarded this distinction warrant particular protection for their visitors, which is a particular point of tourism attractiveness: the result, they are preferred by tourists and, therefore, by tour operators selling tourism packages for the littoral. In 2009, Romanian beaches were not awarded any Blue Flags.